Learning retention in mathematics over consecutive weeks: Impact of motivated forgetting - Julius Valderama; Jubert Oligo (International Journal of Evaluation and Research in Education (IJERE), 2021)
Retention is the ability to retain information in the mind, either in short-term or long-term memory. Memory in the long-term is more ideal. Thus, this has become a challenge for educators on how to transfer ideas in short-term memory to long-term memory. To concretize the effect of time on mathematics learning retention, a randomized pre-test post-test x groups design, using matched subjects was used in the study. Seven matched groups of students were identified, and took the pre-test as the basis of the initial amount of learning, after which a group of students was assigned to take the post-test every week for seven weeks. The post-tests results were the basis of the amount of retained learning of the students. The study found out that: i) The amount of retained learning among the students diminished following a negative exponential curve; ii) The amount of retained learning was comparably equal with the initial amount of learning up to the second week; iii) The amount of retained learning became incomparable with the initial amount of learning after the third week; and iv) The concepts in the knowledge level had a great chance to be remembered while the concept with analysis level was prone to motivated forgetting.